1990
DOI: 10.1128/iai.58.6.1496-1499.1990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vivo T-cell depletion on the effector T-cell function of immunity to Eimeria falciformis

Abstract: BALB/c mice were exposed to the enteric parasite Eimeria falciformis to produce a natural acquired immunity. The mice were then depleted of their effector T-cell function by in vivo administration of a cytotoxic Thy-1.2 mouse monoclonal antibody. T-cell depletion was demonstrated by a reduction in concanavalin A-induced proliferation of splenic lymphocytes in treated mice compared with that in controls. Twenty-four hours following T-cell depletion, the mice were challenged with 5,000 oocysts of E. falciformis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The increase of CD4 cells that we found after primary infection suggests that these cells together with macrophages are involved in the induction of the immune response, whereas the increase of CD8 cells after challenge infection suggests that these cells act as effector cells. The correlation between our findings concerning the changes in LPL subsets and the results found after depletion and transfer studies in mice (Rose et al 1988a, 1988b, Stiff & Vasilakos 1990) suggest comparable immune responses to different Eimeria spp. However, immunity to reinfection is species specific since cross-protection between spp.…”
supporting
confidence: 85%
“…The increase of CD4 cells that we found after primary infection suggests that these cells together with macrophages are involved in the induction of the immune response, whereas the increase of CD8 cells after challenge infection suggests that these cells act as effector cells. The correlation between our findings concerning the changes in LPL subsets and the results found after depletion and transfer studies in mice (Rose et al 1988a, 1988b, Stiff & Vasilakos 1990) suggest comparable immune responses to different Eimeria spp. However, immunity to reinfection is species specific since cross-protection between spp.…”
supporting
confidence: 85%
“…Athymic mice and rats experience more severe primary infections and have no resistance to reinfection (83). Furthermore, a partial in vivo depletion of mouse T cells with antibody to Thy 1.2 antigen resulted in an abrogation of protective immunity to E. falciformis and extended the patent period (105). Similarly, depletion of CD4 ϩ cells by in vivo treatment with anti-CD4 MAb increased the severity of primary E. vermiformis infection but had no effect in animals with established immunity (88).…”
Section: Host Immune Responsesmentioning
confidence: 99%
“…T cells have been shown to play a major role in the defense against E . falciformis infection (Mesfin & Bellamy, 1979; Stiff & Vasilakos, 1990). Following infection, interferon γ (IFNγ) is upregulated (Schmid et al, 2013) and experimental infections showed higher weight loss and pathology but lower oocysts shedding in IFNγ‐deficient mice than in wild type (Stange et al, 2012).…”
Section: Eimeria Spp As New Model Parasites To Assess Resistance Heal...mentioning
confidence: 99%
“…Host defense mechanisms against this parasite are well studied (Mesfin & Bellamy, 1979;Pogonka et al, 2010;Schmid et al, 2013) and its whole genome is sequenced and annotated (Heitlinger et al, 2014). T cells have been shown to play a major role in the defense against E. falciformis infection (Mesfin & Bellamy, 1979;Stiff & Vasilakos, 1990). Following infection, interferon γ (IFNγ) is upregulated (Schmid et al, 2013) and experimental infections showed higher weight loss and pathology but lower oocysts shedding in IFNγ-deficient mice than in wild type (Stange et al, 2012).…”
Section: Ei M Eria S Pp a S Ne W Model Par A S Ite S To A Ss E Ss Re ...mentioning
confidence: 99%